MANAJEMEN PUNCAK DAN PEMANFAATAN TEKNOLOGI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI (Studi Kasus di Rumah Sakit PKU Muhammadiyah Surakarta) - Yanesti Putri Mumpuni; Yuniatin TDKW (ADVANCE, 2018)
This study aims to determine the effect of user participation, the influence of top management support and utilization of technology on the effectiveness of accounting information systems in PKU Muhammadiyah Surakarta Hospital. Data collection methods of this study were collected by filling out questionnaires distributed directly to the accounting and finance department employees of PKU Muhammadiyah Surakarta Hospital. The results of the analysis show that the validity and reliability of all the questions asked are proven to be valid and reliable. The results of the classic assumption test show that this study is normally distributed, there is no multicollinearity, autocorrelation does not occur and heteroscedesity does not occur in the regression model. The regression results of this study prove that User Participation, Top Management Support, and Technology Utilization have a positive effect on the Effectiveness of Accounting Information Systems. The results of the t test show that User Participation, Top Management Support, and Technology Utilization have a significant effect on the Effectiveness of Accounting Information Systems. The F test results show that User Participation, Top Management Support, and Technology Utilization together have a significant effect on the Effectiveness of Accounting Information Systems. The results of the R^2 test indicate that the variable User Participation, Top Management Support, and Technology Utilization can explain the Accounting Information System variable by 65.8% while the remaining 34.2% is influenced by other variables not included in this research, such as personal capability. company size, and location of the information system department.Keywords: user participation, top management support, technology utilization, effectiveness of accounting information systems.